THE IMPACT OF FOREST FIRES ON TIMBER PRODUCTION AND FOREST ECOSYSTEMS - Megan Koh; Ava Lee; Ryan Teo (Journal of Selvicoltura Asean, 2025)
Forest fires are a significant environmental issue, especially in tropical regions, where they have been known to disrupt ecosystems and hinder sustainable timber production. The increasing frequency and intensity of forest fires, driven by both natural causes and human activity, pose a major threat to forest health and biodiversity. Additionally, the economic impact on the timber industry is profound, with fires damaging forests, destroying timber resources, and reducing overall timber yields. This study investigates the effects of forest fires on timber production and forest ecosystems, focusing on their long-term consequences. This research aims to assess the impact of forest fires on timber production, as well as the broader effects on forest ecosystems, including biodiversity loss, soil degradation, and carbon emissions. The study also seeks to explore potential mitigation strategies for reducing fire risks and promoting the recovery of forest ecosystems post-fire. A mixed-methods approach was employed, combining remote sensing data, field surveys, and interviews with forestry experts and local communities. The study analyzed fire-affected areas in Southeast Asia, comparing timber production data before and after fire events. Ecological indicators, such as species diversity and soil quality, were also measured to assess the impact on the forest ecosystem. The findings show a significant decline in timber production following forest fires, with affected areas showing reduced growth rates and a lower timber yield in the years after the fire. Forest ecosystems also experienced biodiversity loss, with long-term degradation of soil quality and carbon sequestration capacity. Forest fires have a substantial negative impact on both timber production and forest ecosystems. Effective fire management strategies are crucial for minimizing damage and supporting the recovery of forest resources and biodiversity.